Integrating Digital Skills Competencies into Professional Diploma in Education Curriculum in Vocational and Technical Education in North-East Nigeria - Umoru, Mohammed Lawal; Ibanga, Isaac John; Sunday, Philip (Lembaga Yasin AlSys, 2024)
The main aim of the study was to integrate digital skills competencies into Professional Diploma in Education curriculum in Vocational and Technical Education in North-East Nigeria. The study was guided by three research questions and three hypotheses. The study adopted a survey research design was carried out in northeast Nigeria. The population of the study was 1485 comprising 993 Vocational and Technical Education lecturers from 9 Colleges of Education (COEs) where PDE are undertaken in the northeast, 210 ICT experts from the 9 COEs, and 182 Education Supervisors from the Ministry of Education in the six States of the Northeast. The study adopted Simple random sampling and a sample size of 317 respondents was determined using Krejcie and Morgan (1970) sample size table. A structured questionnaire was utilized to gather data for the study. The questionnaire was validated by three experts and a reliability index of 0.86 was obtained using Cronbach Alpha after a trial test. The data for the study was analyzed using mean and standard deviation to answer the research questions while ANOVA was used to test the hypotheses at 0.05 l3v3l of significance. The study revealed that 26 digital skills competences, 26 general performance objective as well as 26 specific objectives each grouped into 8 clusters were found relevant for inclusion into the vocational and technical Professional Diploma in Education (PDE) curriculum in northeast, Nigeria. It was recommended that The National Commission for Colleges of Education (NCCE), and the National Teachers Institute (NTI) should adopt the identified digital competencies into the PDE curriculum of the Vocational and Technical Education curriculum; and the NCCE and NTI should update the curriculum guidelines and standards to explicitly include digital skills competencies as essential components of the PDE curriculum in vocational and technical education.